1980
DOI: 10.1042/cs059311s
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Noradrenaline Uptake, Spillover to Plasma and Plasma Concentration in Patients with Essential Hypertension

Abstract: 1. The rates of entry of noradrenaline to plasma and of removal of noradrenaline from plasma, and plasma noradrenaline concentration, were determined in normal subjects and in patients with essential hypertension. Neuronal uptake of noradrenaline was assessed from the plasma tritiated noradrenaline disappearance curve, after infusion to steady state. 2. Noradrenaline disappearance was biexponential. Rapid removal was dependent on neuronal uptake, being slowed if neuronal noradrenaline uptake was reduced, eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Additional factors influencing the plasma NE levels include variation in distribution and rate of metabolism, which VOL 5, No 1, JANUARY-FEBRUARY 1983 is seen in normal subjects, 32 hypertensive patients, autonomic insufficiency, and following drug interventions. 33 It may be for this reason that there is dispute as to the interrelationship between baseline plasma NE levels and the presence and extent of hypertension. 22 ' 3K 34~36 However, plasma NE levels are considered to be representative of sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors influencing the plasma NE levels include variation in distribution and rate of metabolism, which VOL 5, No 1, JANUARY-FEBRUARY 1983 is seen in normal subjects, 32 hypertensive patients, autonomic insufficiency, and following drug interventions. 33 It may be for this reason that there is dispute as to the interrelationship between baseline plasma NE levels and the presence and extent of hypertension. 22 ' 3K 34~36 However, plasma NE levels are considered to be representative of sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 99%
“…A few other groups of investigators have compared plasma NE disappearance in hypertensive and normotensive groups (22,23,27,28) after an infusion to steady state, with discrepant results. Esler and coworkers found that the first half-life of NE disappearance is prolonged in a minority of patients with essential hypertension (22), which they attributed to decreased U1 (29).…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to measure separately the contributions of these factors in determining plasma NE in patients with essential hypertension, Esler and associates (22,23) early, rapid half-life (t1/20) of -2 min and later with a slower half-life (t1/2b) of >30 min; that desipramine prolonged t1/2a; and that a subgroup of hypertensive patients showed prolongation of t1/2a. They concluded that in some patients with essential hypertension, faulty U, could account for elevated circulating levels of NE and the patients' high blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in studies in which the neuromuscular junction has been assessed in essential hypertension by measurements of the rate at which [ 3 H]norepinephrine is removed from the plasma, there is evidence of an impairment in the neuronal uptake of norepinephrine. 35 " 37 The reason for this lack of effect of cocaine is currently difficult to explain. In other experiments in our laboratory we have found that cocaine in cannulated and pressurized vessels has no effect on the concentration-response relation of norepinephrine in rat mesenteric vessels from both spontaneously hypertensive and normotensive Wistar-Kyoto rats, whereas on the wire myograph the concentration-response curves are shifted to the left (unpublished data).…”
mentioning
confidence: 99%